Diagnostic Accuracy of Ascites Fluid Gross Appearance in Detection of Spontaneous Bacterial Peritonitis - Aminiahidashti, Hamed; Hosseininejad, Seyed Mohammad; Montazer, Hosein; Bozorgi, Farzad; Goli khatir, Iraj; Jahanian, Fateme; Raee, Behnaz (Archives of Academic Emergency Medicine, 2014)
Introduction: Spontaneous bacterial peritonitis (SBP) as a monomicrobial infection of ascites fluid is one of the most important causes of morbidity and mortality in cirrhotic patients. This study was aimed to determine the diagnostic accuracy of ascites fluid color in detection of SBP in cirrhotic cases referred to the emergency department.Â Methods:Â Cirrhotic patients referred to the ED for the paracentesis of ascites fluid were enrolled. For all studied patients, the results of laboratory analysis and gross appearance of ascites fluid registered and reviewed by two emergency medicine specialists. The sensitivity, specificity, positive and negative predictive value, and positive and negative likelihood ration of the ascites fluid gross appearance in detection of SBP were measured with 95% confidence interval.Â Results: The present project was performed in 80 cirrhotic patients with ascites (52.5 female). The mean of the subjectsâ€™ age was 56.25Â±12.21 years (35-81). Laboratory findings revealed SBP in 23 (29%) cases. Fifty nine (73%) cases had transparent ascites fluid appearance of whom 17 (29%) ones suffered from SBP. From 21 (26%) cases with opaque ascites appearance, 15 (71%) had SBP. The sensitivity and specificity of the ascites fluid appearance in detection of SBP were 46.88% (Cl: 30.87-63.55) and 87.50% (95% Cl: 75.3-94.14), respectively.Â Conclusion:Â It seems that the gross appearance of ascites fluid had poor diagnostic accuracy in detection of SBP and considering its low sensitivity, it could not be used as a good screening tool for this propose.